P92 Improving Diagnosis And Management Of Patients With Copd In The Acute Medical Admission Unit: A "right Care" Approach. (10th November 2014) - Rutter-Locher, Z; Patel, V; Taylor, K; Kelly, P; Patel, I
Abstract : Introduction: COPD is the second most common cause of emergency admission and 5th cause of readmission to hospital. Appropriate identification and treatment is crucial to make every bed day count and reduce the burden of COPD. Characterising COPD exacerbations (ECOPD) and excluding differential diagnoses in acutely unwell co-morbid patients can be challenging. This study aimed to evaluate the accuracy of diagnoses/management of patients on the acute medical unit (AMU) in an inner London teaching hospital with 300 ECOPD admissions/yr, and to develop an improvement plan. Methods: Admission records for COPD patients admitted acutely with increased shortness of breath, cough and/or wheeze over 6 weeks (Jan/Feb 2014) were reviewed. Diagnostic criteria and treatment were compared to national standards. 21 AMU junior staff completed a COPD knowledge questionnaire. An ECOPD pathway was developed, highlighting diagnostic and treatment differences between infective (IECOPD), non-infective COPD exacerbations (NIECOPD) and community acquired pneumonia (CAP), supported by electronic prescribing order sets. An online learning module was developed to support junior doctors. Results: 44 COPD patients (26M, 18F) were admitted to AMU. 20% had an incorrect diagnosis. Of NIECOPD patients (20%): 66% received antibiotics; 11% did not receive prednisolone. Of IECOPD patients (47%): 65% received iv or incorrect oral antibiotics; 14% did not receive prednisolone. Of CAP patients (32%): in CURB <3 89% received iv antibiotics. 5 CAP patients were documented as IECOPD; 2 were undertreated. 2 IECOPD patients were diagnosed with CAP and over treated. Only 13/21 (62%) of AMU junior doctors understood the difference between NIECOPD, IECOPD and CAP. After the improvement plan, incorrect diagnosis fell from 20% to 7%. Of NIECOPD patients (28%): only 18% received antibiotic therapy; 100% received prednisolone. Of IECOPD patients (48%): 74% received correct antibiotics; 100% received prednisolone. Of CAP patients (23%): in CURB <3 iv antibiotic use reduced to 50%. Conclusion: COPD patients commonly present acutely with ECOPD, NIECOPD or CAP. This can cause diagnostic uncertainty in an AMU setting. A right care approach focusing on accurate diagnosis first time and guideline based therapy, supported by joint working, education and electronic prescribing can improve staff knowledge and patient management.